2017
DOI: 10.1080/14686996.2016.1275784
|View full text |Cite
|
Sign up to set email alerts
|

Solid lubricant behavior of MoS2 and WSe2-based nanocomposite coatings

Abstract: Tribological coatings made of MoS2 and WSe2 phases and their corresponding combinations with tungsten carbide (WC) were prepared by non-reactive magnetron sputtering of individual targets of similar composition. A comparative tribological analysis of these multiphase coatings was done in both ambient air (30–40% relative humidity, RH) and dry nitrogen (RH<7%) environments using the same tribometer and testing conditions. A nanostructural study using advanced transmission electron microscopy of the initial coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 39 publications
(38 reference statements)
1
29
0
Order By: Relevance
“…The intensive and narrow peak at 2~ 44.5° was due to reflection from the steel substrate. The diffractograms of the MoS2 coatings were similar in many respects to those measured for transition metal-dichalcogenide-based coatings obtained through ion sputtering or PLD at room temperature [19,21,22,38]. The XRD patterns of these coatings showed an intense and broad peak near 2~ 13° and a pronounced peak at 2~ 33°, followed by a broad peak at 2~ 43°.…”
Section: The Structure and Composition Of Mos X Filmssupporting
confidence: 61%
See 2 more Smart Citations
“…The intensive and narrow peak at 2~ 44.5° was due to reflection from the steel substrate. The diffractograms of the MoS2 coatings were similar in many respects to those measured for transition metal-dichalcogenide-based coatings obtained through ion sputtering or PLD at room temperature [19,21,22,38]. The XRD patterns of these coatings showed an intense and broad peak near 2~ 13° and a pronounced peak at 2~ 33°, followed by a broad peak at 2~ 43°.…”
Section: The Structure and Composition Of Mos X Filmssupporting
confidence: 61%
“…The most common structural state of deposited coatings is "amorphous", which is generally assumed to form from nanoclusters with a lamellar structure typical of the 2H-MoS 2 phase [19][20][21][22]. Friction sliding is associated with the tribo-induced crystallization of such coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is also suggestive that the edge sites play an important role in the humidity dependence. Moreover, it was reported that the friction and wear of MoSe 2 and WSe 2 are hardly influenced by ambient humidity [123,124]. The chemistry of disulfide and diselenide materials in humid environments appear to be drastically different.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…Charge density difference at a distance of z = 2.8 Å (left panels) and z = 3.1 Å (right panels) at the point (x, y) = (0, 1.45) Å as defined inFigure 1. Countour plots at three heights (BN sheet (1), topmost Au layer(3), and the midplane between the two materials (2)) are also shown together with the plane-averaged charge density difference. On the plane-averaged Δρ plots the three planes are marked with vertical lines.…”
mentioning
confidence: 99%